Speech act analysis of interpersonal response on success and failure in the classroom - Boonyanuch Puthornjai (เชียงใหม่ : บัณฑิตวิทยาลัย มหาวิทยาลัยเชียงใหม่, 2020)
This research study was conducted to examine the undergraduate students’ interpersonal responses in Thai classroom conversations to find out how they respond to questions and to analyze the response interpretations indicating success and failure in the classroom. The concept of John Austin’s Speech Act Theory was the framework employed in the analysis The study found out that a locutionary act corresponded to a direct response and could identify success or failure by language use as a linguistic device whereas an illocutionay act corresponded to an indirect response and could identify success and failure through an interpretation of the response. The occurrence of perlocutionary acts was not relevant to this study. The students responded both directly and indirectly. The direct responses were stated in direct assertion patterns whereas the indirect responses were stated in the cooperative component pattern, the satisfaction pattern, and the briefing pattern. The responses were also classified as success responses, failure responses, and additional responses. The additional responses were further sub-classified as partial success–partial failure responses and uncertain responses.